2017
DOI: 10.1186/s13148-017-0333-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the MethylationEPIC BeadChip for fresh-frozen and formalin-fixed paraffin-embedded tumours

Abstract: DNA methylation is the most studied epigenetic modification due to its role in regulating gene expression, and its involvement in the pathogenesis of cancer and several diseases upon aberrations in methylation. The method of choice to evaluate genome-wide methylation has been the Illumina HumanMethylation450 BeadChip (450K), but it was recently replaced with the MethylationEPIC BeadChip (EPIC). We therefore sought to validate the EPIC array in comparison to the 450K array for both fresh-frozen (FF) and formali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 17 publications
5
46
2
Order By: Relevance
“…Pidsley et al showed that correlation between 450K and EPIC for two of the same samples of both cancerous and non-cancerous cell lines across all overlapping sites was high (r >0.9) and that reproducibility for identifying differentially methylated positions (DMPs) between cancer and non-cancerous cells (n = 3 pairs) was excellent, using FDR P  <0.01. Kling et al also reported high overall correlations between EPIC and 450K in both fresh-frozen and formalin-fixed paraffin embedded tumors [3]. Similar results were reported for overall correlation in adult whole blood (n = 145); however, low correlation was observed for many individual sites (55% with r <0.2) and were found to correspond with the variance or range of methylation at a site [4].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Pidsley et al showed that correlation between 450K and EPIC for two of the same samples of both cancerous and non-cancerous cell lines across all overlapping sites was high (r >0.9) and that reproducibility for identifying differentially methylated positions (DMPs) between cancer and non-cancerous cells (n = 3 pairs) was excellent, using FDR P  <0.01. Kling et al also reported high overall correlations between EPIC and 450K in both fresh-frozen and formalin-fixed paraffin embedded tumors [3]. Similar results were reported for overall correlation in adult whole blood (n = 145); however, low correlation was observed for many individual sites (55% with r <0.2) and were found to correspond with the variance or range of methylation at a site [4].…”
Section: Introductionsupporting
confidence: 52%
“…Prior studies have examined reliability and reproducibility of overlapping EPIC and 450K probes in matched samples of cancer tissue [1,3] and adult whole blood [4]. Pidsley et al showed that correlation between 450K and EPIC for two of the same samples of both cancerous and non-cancerous cell lines across all overlapping sites was high (r >0.9) and that reproducibility for identifying differentially methylated positions (DMPs) between cancer and non-cancerous cells (n = 3 pairs) was excellent, using FDR P  <0.01.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the correlation between the arrays, the Pearson correlation coefficient was calculated per sample for the 370,699 probes common to both arrays and passing quality filters. Corroborating previous studies [3,4,6,8], we found that the per sample correlation of methylation -value was high. A 450K vs EPIC scatter plot of methylation -value for one cartilage sample illustrates that the overall correlation was high (Pearson's r 0.99) although many CpGs show greater than 5% difference between arrays (Fig.…”
Section: Overall Sample Correlation Between 450k and Epic Arrayssupporting
confidence: 89%
“…However, methylome analysis using FFPE samples is challenging because the cross‐linking and fragmentation resulting from formalin fixation reduces the quantity and quality of the DNA . Although a previous report has described use of the Infinium assay employing the EPIC array after DNA restoration in FFPE samples, a large amount of genomic DNA (500 ng or 1 μg) was required . In another study using the Infinium 450 k array, which was the previous version of the EPIC array, data from 50 ng of DNA input from a FFPE sample were correlated with those from a matched FF sample, but the impact of the restoration reaction was not discussed .…”
mentioning
confidence: 99%
“…2 Although a previous report has described use of the Infinium assay employing the EPIC array after DNA restoration in FFPE samples, a large amount of genomic DNA (500 ng or 1 mg) was required. 3 In another study using the Infinium 450 k array, which was the previous version of the EPIC array, data from 50 ng of DNA input from a FFPE sample were correlated with those from a matched FF sample, but the impact of the restoration reaction was not discussed. 4 Therefore, the feasibility of the Infinium assay using the EPIC array and the impact of the restoration reaction on very small amounts of genomic DNA from FFPE samples have remained unknown.…”
mentioning
confidence: 99%